Color fundus photograph registration based on feature and intensity for longitudinal evaluation of diabetic retinopathy progression - Zhou, Jingxin; Jin, Kai; Gu, Renshu; Yan, Yan; Zhang, Yueyu; Sun, Yiming; Ye, Juan (Frontiers in Physics, 2022)
Longitudinal disease progression evaluation between follow-up examinations relies on precise registration of medical images. Compared to other medical imaging methods, color fundus photograph, a common retinal examination, is easily affected by eye movements while shooting, for which we think it’s necessary to develop a reliable longitudinal registration method for this modality. Thus, the purpose of this study was to propose a novel registration method for longitudinal color fundus photographs and establish a longitudinal retinal registration dataset. In the proposed algorithm, radiation-variation insensitive feature transform (RIFT) feature points were calculated and aligned, followed by further refinement using normalized total gradient (NTG). Experiments and ablation analyses were conducted on both public dataset and private dataset, using mean registration error and registration success plot as main evaluation metrics. Results showed that our proposed method was comparable to other state-of-the-art registration algorithms and especially accurate for longitudinal images with disease progression. We believe the proposed method will be beneficial for longitudinal evaluation of fundus images.